Ionic cross‐linking of water‐soluble polyurethane improves protein encapsulation and release. Issue 4 (30th March 2015) - Mattu, Clara; Wang, Tianran; Siri, Armida; Sartori, Susanna; Ciardelli, Gianluca
<x xml:space="preserve">Abstract</x> Polymer nanoparticles (NPs) are promising systems for the delivery of protein drugs, as they enhance circulation half‐life, reduce degradation, and increase selectivity of the encapsulated agent. Among the different methods for the preparation of protein‐loaded NPs, ionotropic gelation—which exploits cross‐linking between charged groups in the polymer and counterions in the protein solution—has been extensively investigated for chitosan NPs. The present study aims at exploring the possibility to apply the method to prepare BSA‐loaded polyurethane NPs. A poly(ε‐caprolactone)/poly(ethyleneglicol)‐based polyurethane bearing tert‐butyloxycarbonyl‐protected amino groups was synthesized by a two‐step synthesis procedure. Amino functionalities were exposed under acidic conditions, as confirmed by ninhydrin assay, and then exploited to obtain ionic cross‐linking with sodium tripolyphosphate counterions. The effect of polymer and sodium tripolyphosphate concentration on particles size and BSA encapsulation has been investigated, showing that the PUR concentration plays a major role. Small particles, at 300 nm, with high BSA loading (90%) have been obtained. Sustained BSA release and low burst effect (20%) have been observed, indicating good interaction between the protein and the polymer matrix. The study highlights the possibility of introducing alternative polymers to improve loading and release of proteins from NPs obtained through the ionotropic gelation method.